2009
DOI: 10.14236/ewic/ease2009.3
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Validation of a Requirements Engineering Process Guide

Abstract: Current requirements engineering (RE) practice in industry lacks the availability of an integrated guide that defines and supports the requirements engineering part of embedded system development. Therefore, the RE part of a development project is not as structured and defined as desired. This paper presents results of an experiment validating a RE guide developed by a joint research project between industry and academia. In the experiment carried out for 14 weeks, embedded development projects using the guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…EPGs have been posited for overcoming the natural limitations of printed documents or their digital versions (without a specific EPG design), which are: deficient in form and content, difficult to understand, to use and to access, and scarcely used in practice (Kellner et al, 1998;Hauck et al, 2008;Leuser et al, 2009). Research findings on EPGs has found benefits of their utilization such as: training and process execution improvement (Kellner et al, 1998); gradual tailoring of process, reuse, process conformance, resulting in better process management (Becker-Kornstaedt, 2000); and process communication improvement (Koolmanojwong et al, 2008).…”
Section: Electronic Process Guidesmentioning
confidence: 99%
See 4 more Smart Citations
“…EPGs have been posited for overcoming the natural limitations of printed documents or their digital versions (without a specific EPG design), which are: deficient in form and content, difficult to understand, to use and to access, and scarcely used in practice (Kellner et al, 1998;Hauck et al, 2008;Leuser et al, 2009). Research findings on EPGs has found benefits of their utilization such as: training and process execution improvement (Kellner et al, 1998); gradual tailoring of process, reuse, process conformance, resulting in better process management (Becker-Kornstaedt, 2000); and process communication improvement (Koolmanojwong et al, 2008).…”
Section: Electronic Process Guidesmentioning
confidence: 99%
“…Table 1 reports the study, the domain area, the type of research approach, the research setting, and main finding. In particular, we are interested in the experimental studies (Lott, 1997;McDonald and Miller, 1998;Koolmanojwong et al 2008;Leuser 2009). In Lott (1997) a repeated-measures experimental design with 20 individuals is reported in the context of Software Engineering process guidance.…”
Section: Experimental Studies On the Utilization Of Epgsmentioning
confidence: 99%
See 3 more Smart Citations